PELAKSANAAN PENGAWASAN BALAI PENGAWAS OBAT DAN MAKANAN KEPULAUAN RIAU TERHADAP PENERAPAN STANDAR MUTU PRODUK AIR MINUM DALAM KEMASAN DI KOTA TANJUNGPINANG - Wijaya, Ilham (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2016)
The drinking water is one of the basic needs of living things , as well as the primary need forhuman. Along with the development, the practicality of obtaining the necessities of life increasinglyused as a necessity to pursue efficiency.Thus , the need for drinking water , in innovate into thebottled water ( ADMK ) in order to meet the drinking water needs of the community in a shorttime . Center for Food and Drug Administration RI is a central government agency whose task isto carry out government duties in the field of food and drug supervision in accordance with theprovisions of the legislation in force .The purpose of this study was to determine the tasks,Assessment, and action BPOM Riau Islands in fixing bottlenecks in quality control of productsbottled in Tanjungpinang. Informants used is a number of people consisting of representativesBPOM, business agent AMDK and Society. This research analysis techniques use traditionaltechniques of descriptive analysis with qualitative approach. The results of the ImplementationMonitoring BPOM Riau Islands Against Application of Standards of Quality Products AMDK inTanjungpinang with the results of research that supervision means food processing (AMDK) is aroutine activity undertaken BPOM in order to monitor the application of the mode of production ofprocessed food conducted by both the food industry through monitoring framework pre market andpost using standard checklists, and still their discrepancies with the reality in the field, anassessment of the data is the data obtained in measuring the existing problems in the field, and theresults are still not in accordance with the assessment of the reality on the ground. evaluation of theassessment results have been obtained by assigning ratings with a new method that is based on arisk-based approach to the method. Conclusions and Recommendations which researchers give forcompanies manufacturers of bottled water should still follow any control measures that have beenheld by the BPOM Riau Islands, people who have shop or store that sells products AMDKsebagusnya remain vigilant about the quality control of products sold, and for the government inBPOM this case represented by the Riau Islands in order to improve the standard of supervision inaccordance with the existing needs in the field by constantly evaluating existing assessment systemand tools used in surveillance tools.